Single Center Observational Study to Evaluate the Safety and Efficacy of Self-expanding Composite Mesh for Repair of Small Umbilical Hernias (Journal of Surgical Sciences, 2021)
Background: There is evidence that mesh repair for umbilical hernias results in fewer recurrences. Early and late complication rates of mesh repair are variable with different techniques of mesh repair. In recent years, several mesh device for the repair of small ventral hernias have been developed, but some reports have been published reporting some adverse outcomes like high recurrences or wound related complications encountered with those mesh devices. The purpose of this study was to evaluate the safety and efficacy of small umbilical hernia(